2021
DOI: 10.31024/ajpp.2021.7.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous extract of Clerodendrum thomsoniae Linn. leaves on the onset of hyperlipidaemia and the inhibition of gain mass on wistar rats

Abstract: Background: The genus Clerodendrum is among the most important in the plants' kingdom with many species known for their medicinal properties and among which is well represented. Previous studies Clerodendrum thomsoniae established hypolipidemic, antioxidant and antidiabetic properties of aqueous extract (AECT) of Clerodendrum thomsoniae.This study aimed at evaluating the effect of the AECT on the onset of hyperlipidaemia in wistar Objective: rats.Normal Wistar rats were administered AECT (312.5, 625 and 1250 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In line, from George et al (2021) avocado seed consisted bioactive phenol as a bioactive compound that help to reducing the negative bacteria, make stable environment, and as an anti-tumor. Another study found from Martial et al (2021) showed that clerodendrum consisted antihyperlipidemic that help to reducing the amount of negative microorganism and help increasing number of villi in the intestinal.…”
Section: Discussionmentioning
confidence: 99%
“…In line, from George et al (2021) avocado seed consisted bioactive phenol as a bioactive compound that help to reducing the negative bacteria, make stable environment, and as an anti-tumor. Another study found from Martial et al (2021) showed that clerodendrum consisted antihyperlipidemic that help to reducing the amount of negative microorganism and help increasing number of villi in the intestinal.…”
Section: Discussionmentioning
confidence: 99%